BUILDING OF PERSONNEL POLICY AS AN INSURANCE OF EFFECTIVE ECONOMIC SAFETY ON ENTERPRISES - Dykan, Valeriia; Gladukh, Maryna (Social Economics, 2018)
The article deals with the problems and principles of ensuring the personnel policy of Ukrainian enterprises. The essence of the personnel policy, the main directions in the work with the personnel, its influence on ensuring the economic security of the enterprise is researched. In the external environment are considered. The personnel policy provision is based on organizational integration, functionality, responsibility of all employees at the enterprise and adaptation to continuous training. The experience of personnel policy of leading foreign and Ukrainian companies is analyzed. It is determined that foreign companies accumulate in their personnel policy those principles and elements that are adequate for a particular country and the type of company’s activity. It is determined that in foreign companies work with personnel is based on a clear system of explanation to the company’s employees of indicators and strategies of the company and competence development, opportunities for growth of employees; program and reward system that promote flexibility and balance between work and personal life through the use of part- time employment, flexible work schedules and redistribution of official duties. It was analyzed that main goal of personnel policy of Ukrainian enterprises is implementation of programs for raising staff; retraining and involvement of young specialists; objective data on education; rational use of personnel; creation of favorable conditions for creative initiative and individual work and improvement of material incentives; fixing clear criteria; the transition from the old system of involvement through a practical assessment of the skills of candidates for positions; availability of academic degree; possession of foreign languages; the presence of rewards or punishment.